WORKSHOP ON DEVELOPING INTERACTIVE LEARNING MEDIA FOR GURU PENGGERAK USING ARTICULATE STORYLINE 3 IN BANDUNG - Dahlan, Taufiqulloh; Dheni Harmaen; Acep Roni Hamdani; Erni Kustiani (Pasundan International of Community Services Journal (PICS-J), 2024)
This community engagement program (PKM) is designed to support "Guru Penggerak" in Bandung in creating interactive multimedia-based learning materials through the use of the Articulate Storyline 3 application. The implementation of interactive multimedia learning media is anticipated to enhance both the effectiveness of teaching and student participation. The program is carried out in several phases, including introductory training, practical workshops, technical guidance, and result evaluation. Findings from this initiative indicate an improvement in the teachers’ ability to utilize Articulate Storyline 3 to produce more engaging and interactive instructional content. Furthermore, the program contributes to strengthening teachers’ skills in integrating educational technology in accordance with the demands of the digital era.